TROPICAL BUILDINGSâ PASSIVE STRATEGIES FOR HERITAGE BUILDINGS IN BANDUNG (CASE STUDY: GEDUNG GAS NEGARA BRAGA AND AULA TIMUR ITB) - Nirmalasari, Dindha
Bandung was one of the major cities during the colonial period of Indonesia. There were many buildings constructed by the Dutch colonial government in the same ambiance, urban planning style, and architectural style with those in The Netherlands. These colonial buildings weren’t built with the consideration of climatic differences between Indonesia and The Netherlands at first; earlier buildings didn’t suit the humid tropical climate of Indonesia, but later on, Dutch colonial buildings were adjusted to the local climate. This research aims to obtain the comparison of passive strategies’ performance between two heritage buildings the early 20th century and the current era, located in the tropical climate, through case studies. The first building is Gedung Gas Negara, designed by Schoemaker in 1919. The second building is Aula Timur ITB designed by Henry Maclaine Pont in 1918. The research begins with literature reviews of the two buildings to identify the types and attributes of the applied passive strategies, which includes the buildings orientation, room organisations, thickness of the walls, building materials, roof designs, and eaves of the buildings. The gathered data are calculated mathematically and modeled to conduct simulations of the buldings in order to know the performance of the applied passive strategies’ performance. The simulations are conducted with Energy Plus to obtain the values of air temperature, mean radiant temperature, and relative humidity of the two buildings during one year. The comparison shows that the air temperature and mean radiant temperature values of Aula Timur ITB is lower than those of Gedung Gas Negara. For the relative humidity values, Aula Timur ITB has the higher value compared to Gedung Gas Negara. After the simulation yields some results, OTTV and RTTV calculation is analysed. The total OTTV of Aula Timur ITB measures at 26.16 watt/m2 and Gedung Gas Negara at 33.56 watt/m2, both values are in compliance with the suggested OTTV value in Indonesia i.e. ? 45 watt/m2. The total RTTV of Aula Timur ITB measures at 8 watt/m2 and Gedung Gas Negara at 14.73 watt/m2, which are in compliance with the suggested RTTV value in Indonesia i.e. ? 45 watt/m2.